Germany - Hargrove, Jim. (Chicago : Children's Press, 1991)
Describes the history, geography, reunification, notable cities, government, and life-styles of Germany.
Includes index.
Booklist.
7.2
5-8
5-9.
Keywords: Germany -- Juvenile literature; Germany; Germany